Financial constraints, migration and inequality - Juliano J. Assunç\~ao; Leandro S. Carvalho (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2005)
Although the self-selection of emigrants is determined by dierences in the returns to education, according to the celebrated Roy model, empirical evidence suggests that migrants tend to be favorably selected. This paper argues that financial con- straints might be useful to explain this controversy. These constraints might impose positive correlations between (i) wealth and education, and (ii) wealth and migra- tion, implying a positive bias in the empirical results. We also show that high levels of migration premium and return to education in the source country explain the migration of middle-class individuals, a situation in which migration increases in- equality in the home country.
Keywords: 330; migration; financial constraints; self-selection; human capital; Internationale Migration; Bildungsertrag; Migrationsforschung